Neutronics analysis of the stellarator-type fusion-fission hybrid reactor based on the CAD optimization method. (January 2021) - Li, Jin-Yang; Gu, Long; Xu, Hu-Shan; Zhang, You-Peng; Yao, Cun-Feng; Yu, Rui; Zhang, Lu; Wang, Da-Wei
Highlights: CAD optimization method is used in converting dense mesh structure to low poly style. CAD optimization method can provide the intuitive and flexible features. Neutronics analysis of the FFHR is performed based on CAD optimization method. Stellarator-type FFHR can keep tritium self-sufficiency and get high breeding ratio. Abstract: The stellarator plasmas devices have some advantages in steady state operation with less magneto hydrodynamic activities, and the development of stellarator-type FFHR (Fusion-Fission Hybird Reactor) can provide viable energy in the foreseeable future with less requirements to the plasmas technology compared with the pure fusion system. However, the neutronics design of the stellarator-type FFHR has some challenges and difficulties, since the construction of helical structures with large number of high order spline surfaces are the extremely complicated process, and the physical parameters of the complex model have to be changed frequently in the primary design stage, which make the corresponding manual input simulation work into the time consuming and error prone tasks. In this context, the CAD optimization method has been used in converting the dense mesh oriented CAD structure to the low poly style, and the CAD-PSFO code has been employed for the modeling transformation process in Monte Carlo calculation. The thorium resource has been selected as the breeding material for the stellarator-type FFHR, and the polonium and natural abundance of uranium have been used as the seed fuel for the initial loading in order to get the high energy multiplication factor. The OMCB (OpenMC based Burnup code) has been introduced to study the burnup features, and stellarator-type FFHR has been designed as the multi-purposes facility that can keep tritium self-sufficiency and get the high breeding ratio with steady energy output.